PENGEMBANGAN PEMBELAJARAN BAHASA INDONESIA MELALUI MODEL KOOPERATIF BERBASIS LIFE SKILL - Asrofah . (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
Developing cooperative model learning stand on several approaches are assumed to be able to improve the student learning process and outcome. The approach is active learning, contructivistic, and cooperative. Those several approaches are integrated to produce a learning model that enable their potential optimally. In order for student with life skill, learning in school emphized the application of science that learn to equip student to know and overcome the issues of life. A learning not only about knowledge knowing, remembering, and understanding, but also directed to creat something useful for life. Indonesian language learning is expected to assist the student get to know them self, their culture, and?é?á the cultures of others, suggest their idea and feel, participate on the society as the language owner and founder, and also use their analitic and imaginative capability. Indonesian language learning directed improve student cammunicate?é?á ability in Indonesian language properly and correctly, either orraly or in writing, and foster an appreciation of literary works. Based on that, student need to be eqquipped with life skills through cooperative learning process. Thus, the expected goals so that student has language skills, can be achieved optimally. Key words: leaning, life skill, cooperative, language leaning aspect.